The Role Of The Statistics And Cryptography Information Communication Services In Advertising Community Services At Baliho, Deli Serdang Regency - Alfi Syahrin; Syukur Kholil (LEGAL BRIEF, 2022)
Mass communication is the dissemination of information to a large audience via communication channels. Mass communication will be defined as the communication of a wide variety to a large audience. The objective of this study is to determine Diskominfostan's role in advertising public services on billboards in Kab. Deli Serdang and the community benefits of public service advertisements on billboards. This descriptive qualitative study examines the role of the Department of Communication, Information, Statistics, and Coding (Diskominfostan) in promoting public services through billboards in the Deli Serdang Regency.